Myocardial m6A regulators in postnatal development: effect of sex - Semenovykh, D; Benak, D; Holzerova, K; Cerna, B; Telensky, P; Vavrikova, T; Kolar, F; Neckar, J; Hlavackova, M (Physiological research, 2022)
N6-methyladenosine (m6A) is an abundant mRNA modification affecting mRNA stability and protein expression. It is a highly dynamic process, and its outcomes during postnatal heart development are poorly understood. Here we studied m6A machinery in the left ventricular (LV) myocardium of Fisher344 male and female rats (postnatal days one to ninety; P1-P90) using Western Blot. A downward pattern of target protein levels (demethylases FTO and ALKBH5, methyltransferase METTL3, reader YTHDF2) was revealed in male and female rat LVs during postnatal development. On P1, the FTO protein level was significantly higher in male LVs compared to females.
Keywords: Rats; Female; myokard; Animals; ženské pohlaví; krysa rodu Rattus; mužské pohlaví; Male; Myocardium; zvířata